Hubungan Pengetahuan, Pola Makan dan Tingkat Stress terhadap Kejadian Gastritis pada Siswa di SMK PGRI 2 Cibinong Tahun 2022: The Relationship Between Knowledge, Eating And Stress Levels On The Incidence Of Gastritis In Students At SMK PGRI 2 Cibinong In 2022 - Rika Nurul Azizah; Rahmat Supriyatna; Nur Rizky Ramadhani (Jurnal Interprofesi Kesehatan Indonesia, 2023)
Introduction: The incidence of gastritis is a problem experienced by someone who has been diagnosed by a doctor or someone who has taken gastritis medication. The prevalence of gastritis in Bogor Regency in 2021 will reach 238,452,952 inhabitants or 40.8%. Objectives: The purpose of this study was to determine the relationship between knowledge, diet and stress levels on the incidence of gastritis in students at SMK PGRI 2 Cibinong in 2022 Method: This research uses analytic research with a cross-sectional research design. The number of respondents in this study was 93 respondents. The sampling technique in this study used the Slovin formula. Data collection using a questionnaire. The statistical test used in this study is the Chi-Square Test. Result: The chi-square test results for the relationship between knowledge and the incidence of gastritis obtained a p-value = 0.905. The results of the chi-square test between diet and the incidence of gastritis obtained a p-value = 0.024. The chi-square test results between stress levels and the incidence of gastritis obtained a p-value = 0.008. Conclusion: There is no significant relationship between knowledge and the incidence of gastritis. There is a significant relationship between diet and the incidence of gastritis. There is a significant relationship between stress levels and the incidence of gastritis.